Novel gene variants associated with primary ciliary dyskinesia - KARADAĞ, BÜLENT TANER (My University, 2022)
Objectives To determine the demographic, clinical, and genetic profile of Turkish Caucasian PCD cases. Methods Targeted next-generation sequencing (t-NGS) of 46 nuclear genes was performed in 21 unrelated PCD cases. Sanger sequencing confirmed of potentially disease-related variations, and genotype-phenotype correlations were evaluated. Results Disease-related variations were identified in eight different genes (CCDC39, CCDC40, CCDC151, DNAAF2, DNAAF4, DNAH11, HYDIN, RSPH4A) in 52.4% (11/21) of the cases. The frequency of variations for CCDC151, DNAH11, and DNAAF2 genes which were highly mutated genes in the cohort was 18% in 11 patients. Each of the remaining gene variations was detected once (9%) in different patients. The variants, p.R482fs*12 in CCDC151, p.E216* in DNAAF2, p.I317* in DNAAF4, p.L318P and p.R1865* in DNAH11, and p.N1505D and p.L1167P in HYDIN gene were identified as novel variations. Interestingly, varying phenotypic findings were identified even in patients with the same mutation, which once again confirmed that PCD has a high phenotypic heterogeneity and shows individual differences. Conclusion This t-NGS panel is potentially helpful for exact and rapid identification of reported/novel PCD-disease-causing variants to establish the molecular diagnosis of ciliary diseases.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatrics; Pediatrics, Perinatology and Child Health; Primary ciliary dyskinesia; Targeted next-generation sequencing; Mutation analysis; Ciliary diseases; DIAGNOSIS; MUTATIONS; CCDC40; Primary ciliary dyskinesia; Targeted next-generation sequencing; Mutation analysis; Ciliary diseases